Sudden gait perturbations elicit sex-specific neuromuscular trunk responses in persons with low back pain. (26th March 2020) - Mueller, Juliane; Martinez-Valdes, Eduardo; Mueller, Steffen; Kulig, Kornelia; Mayer, Frank
Abstract: Persons with low back pain (LBP) exhibit delayed trunk muscle onset and increased co-contractions as a response to quasi-static and dynamic sudden trunk loading in comparison to back-healthy controls. Although LBP is more prevalent in females, sex-specific responses have not been well documented. Therefore, the purpose was to explore sex-specific neuromuscular differences, to gait perturbation, in LBP patients. Twenty-nine LBP patients (12m/17f;31 ± 10yrs; 174 ± 12 cm; 71 ± 16 kg) walked on a split-belt treadmill at 1 m/s, while 15 right-sided random perturbations (treadmill-belt decelerating, 40 m/s 2, 50 ms duration; 200 ms after heel contact) were applied. Muscle activity was assessed using a 12-lead surface EMG (6 back/6 abdominal muscles; 4000 Hz). EMG-RMS [%] (0–200 ms after perturbation) was calculated and normalized to RMS of unperturbed gait for each muscle. Furthermore, muscle onsets (ms) were determined. Two-way ANOVA (factors: sex/muscle) was applied to account for sex differences in main outcomes. EMG-RMS (amplitudes; mean) ranged from 356% to 901% in males and 349% to 694% in females representing a significant interaction effect (sex * muscle: p = 0.017). Post-hoc analysis revealed significant differences for EMG-RMS analysis of rectus abdominis left (p = 0.043; f > m) as well as obliques externus right/left (p = 0.018/p = 0.005; f < m). In the time domain, females showed overall, shorter (mean: 90 ± 16 ms) response times compared to males (mean: 98 ± 22 ms, sex effect: p < 0.0001). In this LBP population, abdominal muscle activation discriminated females from males. Specifically, females had higher activity of the rectus abdominis muscles and lower activation of the externus oblique muscles. These different activation strategies might be relevant to the development of sex-specific intervention strategies.